EXPERIMENTAL STUDY ON CRACK GROWTH RATE OF B780CF STEEL WELDED JOINTS UNDER DIFFERENT WELDING PROCESS - SHENG ShouYong; WANG ShiYue; LIU GuoShou; ZHENG YiHua (Jixie qiangdu)
The fatigue crack growth rate under different welding process was tested with standard compact tension specimen,the test data are processed by using incremental polynomial method and the crack growth rate curve under different welding process was obtained. The effect of different welding process on the crack growth rate was analyzed,the result show under the condition of the same crack length,the influence on fatigue life N,base material life < submerged arc welding life < heat affected zone life < manual welding life. and the fatigue fracture under welding process was analyzed,the mechanism of the crack growth rate under different welding process was discussed.